High school geometry / Rachel P. Keniston - Keninston, Rachel P. [et. al] (Massachusetts: Ginn and company, 1960)
Fundamental ideas and terms, fundamental definitions, assumptions, and theorems, use of fundamental facts and ideas in proof, poof and applicatons of theorems, about tringles, paralle lines, polygons, quadrilaterals, circles; measurement of angles in cirles, indirect proof and inequalities, locus, contruction and design, ratio and proportion, similar polygons, numerical trigonometry and other means of indirect measurement, aresa, regular polygons and circles.
contents, ilustration graphic table squares
Col. Educ
Keywords: 1.GEOMETRIA 2. GEOMETRY 3. FUNDAMENTAL DEFINITIONS 4. EDUCATIÓN